Profits Obtained by Non-Domiciled Legal Entities when they sell Shares of Stock - Hernández Berenguel, Luis (1987)
The text analyzes the tax treatment applicable in Peru to the profits generated by non-domiciled legal entities when disposing of shares of companies incorporated in the national territory. According to the Income Tax (IR) regime, these profits are not subject to taxation, except in specific situations established in the Sole Orderly Text (TUO) approved by Supreme Decree No. 300-85-EF. Such situations include the habitual sale of shares or the fact that these have been received as consideration in operations of a recurring nature. Likewise, in order for such gains to be taxed, they must qualify as Peruvian source income, in accordance with the articles of the TUO that regulate this aspect. Finally, the analysis also addresses previous case law that has influenced the interpretation of this tax treatment, pointing out inconsistencies in its application and evaluation.